A study on the status of public libraries in Laguna - De Ramos, Maria Cristina S.; Santos, Yhna Therese P. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2018)
Libraries in the Philippines have been evaluated before but most of those studies were done decades ago and/or were limited to cities in the NCR. This study aims to ignite the need and want for a nationwide library evaluation in the Philippines by beginning with an evaluation of public libraries in the province of Laguna. The Standards for Philippine Libraries or SPL created by the Professional Regulation Commission (PRC) was used to evaluate the libraries included in this study.
A questionnaire was given to each library and was answered by the head librarian. In the absence of a head librarian, the officer-in-charge was asked to answer the questionnaire. Seven out of the eight public libraries in Laguna answered the questionnaire given to them. Using the data gathered from the questionnaires and the SPL, the public libraries were assessed in terms of missions, goals, and objectives, library administration, human resources, collection development, services and utilization, physical facilities, information technology facilities and services, financial resources, and linkages and networking. Figures, tables, and graphs were used to display and analyze the data. The findings of the study show the strong and weak points of the public libraries in accordance to the SPL.
Based on which libraries met the SPL, the libraries are weak in terms of administration, mission, goals, and objectives, human resources, print collection, non-print collection, security, library services, fund raising, library areas, seating capacity, information technology facilities and services, financial resources, linkages and networking. On the other hand, the libraries are strong in terms of library hours, local historical and cultural materials, community development, library location, transportation to the library, and library access for the disabled. The libraries are neither weak nor strong in terms of organization. All in all, none of the libraries met the SPL.
Thesis
Keywords: Public libraries -- Standards; Public libraries -- Philippines